A history of modern Europe - Merriman, John M. (W.W. Norton, 2004)
A seasoned teacher and talented historian, Professor Merriman offers a carefully crafted narrative that guides students through a vast amount of complex material, integrating the many aspects of the European experience into a larger, interconnected whole. A full 10% shorter than its predecessor, the Second Edition has tightened organization throughout to make room for recent research and descriptions of the current issues and events that define Europe’s role in the world today.